Analysis of Implementation Psychomotor Assessment of Virus Material in SMA/MA/SMK: Urgency of Assessing the Implementation of Healthy Behavior during the COVID-19 Pandemic - Ferdyan, Rhavy; Syamsurizal, Syamsurizal; Lufri, Lufri; Zulyusri, Zulyusri (FMIPA UNNES, 2021)
Biology is a subject that bridges students' knowledge about this pandemic period, where this subject must present knowledge about viruses. In fact, the curriculum designs material that is very detailed and thoroughly discusses viruses found at the SMA / MA / SMK level, but the very minimum requires teachers to evaluate psychomorphic learning related to the application of healthy living habits and preventive efforts to campaign against viruses. Through this article, it will be explained how important psychomotor assessment of this virus is, where the condition of students must first have the competence and do real practicum in preventing virus diseases, especially COVID-19. This article is the result of observations on the implementation of psychomotor assessment, literature review, and documentation studies that give rise to ideas on the importance of psychomotor assessment of virus material in students. Virus material is very important to be presented in biology learning with consideration of a very wide coverage of material (virology), contextual material, the material as a design for health education indicators, and as an indicator design with epidemic response education.